2022
DOI: 10.1177/21925682221079259
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Spinal Epidural Hematoma: Are We Discontinuing Aspirin Early Enough?

Abstract: Study Design Retrospective cohort study. Objectives (1) To compare the risk of Spinal Epidural Hematoma (SEH) associated with specific pre-operative and post-operative anticoagulation (AC) and antiplatelet medications (APM). (2) To define the incidence of SEH and identify risk factors for SEH in our population. Methods Thoracolumbar surgeries between October 2009 and March 2020 were collected. Patients who underwent incision and drainage of a symptomatic SEH were identified. AC and APM was recorded 14 days pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 23 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…They also demonstrated that nonsteroidal anti-inflammatory drugs increased surgical blood loss. Saitta et al found that preoperative aspirin was associated with an increased risk of SEH even when appropriately discontinued in their retrospective cohort study 11) . They also suggested that surgeons should observe these patients more carefully after surgery and consider extending aspirin discontinuation to prevent the serious postoperative complication of SEH.…”
Section: ) Reports Of Increased Hemorrhagic Complications Related To ...mentioning
confidence: 96%
“…They also demonstrated that nonsteroidal anti-inflammatory drugs increased surgical blood loss. Saitta et al found that preoperative aspirin was associated with an increased risk of SEH even when appropriately discontinued in their retrospective cohort study 11) . They also suggested that surgeons should observe these patients more carefully after surgery and consider extending aspirin discontinuation to prevent the serious postoperative complication of SEH.…”
Section: ) Reports Of Increased Hemorrhagic Complications Related To ...mentioning
confidence: 96%
“…The surgical sites were divided into cervical [8,10,11,13,14,19,28,36,37,[40][41][42][43][44][45], thoracic [8,11,13,19,28,31,[40][41][42][44][45][46] and lumbar [5, 8, 9, 11, 13, 16-22, 28, 29, 32-35, 40-42, 44-46] surgery with 15, 12 and 25 studies including 27,779, 16,897, 80,766 patients, respectively, and 72, 104 and 356 patients developed SSEH, respectively. The pooled incidence of SSEH was 0.32% (95% CI 0.002-0.005, P < 0.01, I 2 = 63%) for cervical surgery, 0.84% (95% CI 0.004-0.017, P < 0.01, I 2 = 88%) for thoracic surgery, and 0.63% (95% CI 0.004-0.010, P < 0.01, I 2 = 92%) for lumbar surgery.…”
Section: Surgical Sitementioning
confidence: 99%
“…[2,6,17] Major predisposing factors for pSEH included; perioperative/postoperative coagulation disorders, multilevel spinal surgery, prior spine surgery, and intraoperative cerebrospinal fluid leaks (CSF) [Tables 1 and 3]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The times to onset of symptomatic postoperative pSEH following all-level spine surgery ranged from an average of 2.7 postoperative hours, [1] to less than 24, [2] to between 24-48 postoperative hrs. [5] [Tables 1-4].…”
Section: Introductionmentioning
confidence: 99%
“…[4] The most critical factors to limit/avert permanent neurological sequelae of pSEH included; early recognition of new postoperative neurological deficits, obtaining immediate magnetic resonance imaging (MR) studies, and performing emergency spine surgery where indicated [Tables 1-4]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Incidence of pSEH e incidence of symptomatic postoperative spinal epidural hematomas (pSEH) involving all spinal levels ranged in 7 studies from 0.1% to 1%, [1,2,4,8,9,15,16] in 5 series from <1% to 2.9%, [11,12,15,17,18] and in 3 series between 3%-4.46% (i.e., the 1 of 10 patients with a 10% incidence of pSEH was considered an outlier) [2,6,17] [Tables 1 and 2]. [1][2][3][4][5][6][7][8][9][10]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation